The impact of irrigation on the yield and tuber fraction distribution of potato cultivars - Zsom, E. (International Journal of Horticultural Science, 2006)
Potato is one of the most important plants in human nutrition, it is grown in about 140 countries. As a food, it can be prepared in many ways, it is easily digestable with proteins of high biological value, favourable dietetical-physiological characteristics, high starch content and good taste. An increase in its consumption would be favourable from the dietetical point of view. In Hungary, the growing area of potato has decreased considerably for the last decades and we are lagging behind the Western-European countries regarding yield. The experiments were carried out at the Experimental Site of the University of Debrecen at Látókép between 2002 and 2004. In the large-plot experiment, the yields and the distribution of the tuber fractions were studied for 9 medium early cultivars. The experiment was set up on 50 m2 plots on calcareous chernozem soil. Among the studied cultivars, 3 were of Dutch (Desiree, Kondor, Kuroda) and 6 were of Hungarian breeding (’Góliát’, ’Hópehely’, ’Kankan’, ’Lilla’, ’Százszorszép’, and ’White Lady’). The experiment was set up in 4 repetitions in a randomized design, two of the repetitions were irrigated while two were non-irrigated.